Pendampingan Pola Hidup Bersih Santri Putri Darullughah Wadda’wah Pasuruan - Zunaida, Laily; Abidin, Zainal (Universitas Islam Internasional Darullughah Wadda'wah, 2023)
Darullughah Wadda'wah Islamic Boarding School has health problems that are more or less the same as most Islamic boarding schools. Apart from environmental conditions, another determining factor is the students' habit of always living cleanly. Clean living education among santri is something that is considered difficult for the santri themselves. Apart from having to compete with school time and religious activities, they are required to be able to manage their own rooms. It becomes a very dilemma, when a student who has the habit of keeping his room clean and tidy because the student is already accustomed to a clean and healthy lifestyle, but ends up being influenced by other students who don't care about cleanliness and neatness. Apart from that, the efforts of students who have clean behavior to remind each other will be in vain when students who behave less in maintaining cleanliness consider this to be a thing of the past because they never correct their bad habits and tend to do whatever they want.